2017
DOI: 10.1186/s12885-017-3422-2
|View full text |Cite
|
Sign up to set email alerts
|

Current guidelines for BRCA testing of breast cancer patients are insufficient to detect all mutation carriers

Abstract: BackgroundIdentification of BRCA mutations in breast cancer (BC) patients influences treatment and survival and may be of importance for their relatives. Testing is often restricted to women fulfilling high-risk criteria. However, there is limited knowledge of the sensitivity of such a strategy, and of the clinical aspects of BC caused by BRCA mutations in less selected BC cohorts. The aim of this report was to address these issues by evaluating the results of BRCA testing of BC patients in South-Eastern Norwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
60
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 58 publications
1
60
0
3
Order By: Relevance
“…We have previously estimated that 39% of all BC patients in South Eastern Norway were tested in 2014 and 2015 [21]. In the current study we found that 36.8% of all BC patients (29.8% at IH and 42.6% at Ahus) were offered testing, and that 34.6% (27.8% at IH and 40.2% at Ahus) had been tested.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…We have previously estimated that 39% of all BC patients in South Eastern Norway were tested in 2014 and 2015 [21]. In the current study we found that 36.8% of all BC patients (29.8% at IH and 42.6% at Ahus) were offered testing, and that 34.6% (27.8% at IH and 40.2% at Ahus) had been tested.…”
Section: Discussionsupporting
confidence: 47%
“…We have recently estimated that about 39% of all BC patients in the South-Eastern Norway Regional Health Authority (hereafter called South Eastern Norway) were tested in 2014 and 2015 [21]. However, we do not know how many of the patients who fulfilled the criteria that were offered testing.…”
Section: Introductionmentioning
confidence: 99%
“…Grindedal et al . evaluated the results of BRCA1/2 testing in South‐Eastern Norway and found that 65% of the BRCA1/2 carriers would have been missed if using age of onset below 40 or triple negative breast cancer as criteria for testing . It is also conceivable that, due to an emphasis on disease family history in current guidelines, a smaller family size may compromise the identification of high risk individuals who would otherwise benefit from genetic testing .…”
Section: Discussionmentioning
confidence: 99%
“…Grindedal et al evaluated the results of BRCA1/2 testing in South-Eastern Norway and found that 65% of the BRCA1/2 carriers would have been missed if using age of onset below 40 or triple negative breast cancer as criteria for testing. 40 It is also conceivable that, due to an emphasis on disease family history in current guidelines, a smaller family size may compromise the identification of high risk individuals who would otherwise benefit from genetic testing. 41 In a Swedish retrospective study by Nilsson et al where all breast cancer patients were tested, it was found that while 65% of the BRCA1/2 carriers fulfilled Swedish criteria for testing, only 18% had been identified in regular clinical routine.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence among individuals with a personal and/or family history of breast and/or ovarian cancer is higher, and guidelines for BRCA1/2 testing exist (Moyer, ; National Comprehensive Cancer Network (NCCN), ), but these consensus guidelines are constantly changing based on evolving evidence. Furthermore, with increasing availability and accessibility to cancer genetic testing, it is becoming more evident that the currently commonly utilized testing guidelines might not be sufficiently sensitive for the identification of all individuals/families with a cancer predisposition (Beitsch et al, ; Grindedal et al, ; Li et al, ; Mandelker et al, ).…”
Section: Introductionmentioning
confidence: 99%